(untitled) (Health and Biosciences, 2026)
The hospital pharmacy plays an essential role in patient safety, being responsible for technical-care activities such as selection, storage and dispensing of medicines. Dispensing error, understood as the discrepancy between the prescribed and supplied medicine, is an avoidable incident with the potential to cause significant damage to health. This integrative literature review aimed to identify and systematize effective strategies for the prevention of dispensing errors in hospital pharmacies. The search was carried out in the PubMed and Virtual Health Library (BVS) databases and after applying the eligibility and exclusion criteria, five studies comprised this study. The results showed that the prevention of dispensing errors involves the combined use of light, light-hard and hard technologies. The most effective strategies included reviewing work processes, double-checking potentially hazardous drugs, e-prescribing, implementing automated dispensing systems, standardized patient identification, and strengthening institutional safety culture. The studies pointed to significant reductions in dispensing errors after the adoption of specific protocols and technologies. Automation, although associated with high costs, proved to be cost-effective in the long term, increasing traceability, operational efficiency and freeing up the pharmacist’s time for clinical activities. However, no technology replaces the role of the pharmacist, considered essential in the drug chain and in the promotion of the rational use of medicines. Thus, it is concluded that the strengthening of process management, continuing education, multiprofessional integration and the planned incorporation of technologies are fundamental strategies to reduce dispensing errors and promote patient safety.